IJsland: Verschillen tussen minderheden - Vervoorn, Merijn; Van Tienen, Ines M. K. (Zenodo, 2022)
In most cases, different groups of minorities (Ethnic, Gender, Sexuality, etc.) are all having a hard time. However, in Iceland it is different. Why are there such great differences between minorities? Could this explain why they have the longest running democratic tradition in Iceland? The difference probably stems in the origins of Iceland. Women have always been part of the icelanidc culture, while dark skinned people have not.